Discrete Entailment-Based Linking and -EE Nouns in English - González, Luis (Research in Language, 2007)
Barker (1998) argues that since the referent of an -ee noun can be an indirect object, a direct object, a prepositional object, or a subject, -ee nouns cannot be described as a syntactic natural class. Portero Muñoz (2003) concurs and offers a semantic analysis based on Logical Structure (LS) in the framework of Role and Reference Grammar (RRG). This article proposes that RRG’s macroroles (Actor and Undergoer) can be derived with two entailments and without any need for LS. Its analysis improves Portero Muñoz’s, presenting additional evidence that subjects that allow -ee noun formation are Undergoers. It also explains why most -ee nouns are direct objects in spite of the fact that the suffi Xoriginated as a referent for indirect objects. Finally, it offers an explanation for nouns like amputee, pluckee, twistee, benefactee, malefactee, biographee, catapultee, razee, standee, attendee.